Impaired Feedback Processing for Symbolic Reward in Individuals with Internet Game Overuse - Kim, Jinhee; Kim, Hackjin; Kang, Eunjoo (Frontiers in Psychiatry, 2017)
Reward processing, which plays a critical role in adaptive behavior, is impaired in addiction disorders, which are accompanied by functional abnormalities in brain reward circuits. Internet gaming disorder (IGD), like substance addiction, is thought to be associated with impaired reward processing, but little is known about how it affects learning, especially when feedback is conveyed by less-salient motivational events. Here, using both monetary (±500 KW) and symbolic (Chinese characters “right” or “wrong”) rewards and penalties, we investigated whether behavioral performance and feedback-related neural responses are altered in IGO group. Using functional MRI, brain responses for these two types of reward/penalty feedback were compared between young males with problems of internet-game overuse (IGOs, n = 18, mean age = 22.2 ±2.0 years) and age-matched control subjects (Controls, n = 20, mean age = 21.2 ±2.1) during a visuomotor association task where associations were learned between English letters and one of four responses. No group difference was found in adjustment of error responses following the penalty or in brain responses to penalty, for either monetary or symbolic penalties. The IGO individuals, however, were more likely to fail to choose the response previously reinforced by symbolic (but not monetary) reward. A whole brain 2-way ANOVA analysis for reward revealed reduced activations in the IGO group in the rostral anterior cingulate/ventromedial prefrontal cortex (rACC/vmPFC) in response to both reward types, suggesting impaired reward processing. However, the responses to reward in the inferior parietal (IP) region and medial orbitofrontal/ventromedial prefrontal cortex (mOFC/vmPFC) were affected by the types of reward in the IGO group. Unlike the control group, in the IGO group the reward response was reduced only for symbolic reward, suggesting lower attentional and value processing specific to symbolic reward. Furthermore, the more severe the internet-gaming overuse symptoms in the IGO group, the greater the activations of the ventral striatum for monetary relative to symbolic reward. These findings suggest that IGO is associated with bias toward motivationally salient reward, which would lead to poor goal-directed behavior in everyday life.